Participatory micro-regeneration: governing urban redevelopment in Qinghe, Beijing - Wang, Ying; Wu, Fulong; Zhang, Fangzhu (Urban geography, 2025)
This article explores how far the Foucauldian concept of "governmentality" may offer valuable insights into new trends of participatory regeneration in urban China. Drawing on participatory micro-regeneration projects in Qinghe, Beijing, this research follows a governmentality approach. It explores how the Chinese state exercises new governmental technologies of community participation and self-governance to construct governable spaces and governable subjects. During the regeneration process, we identify multiple participatory practices where citizen power is exercised in decision-making and project implementation but guided by experts within the fields structured by the state. We argue that participation has been instrumentalized by the state to achieve extra-economic objectives of social governance and people-centred development. We also observe tensions and resistance during participatory micro-regeneration, leading to the failure to develop a self-governed community.